Comparison of Automated and Nonautomated Systems for Identification of Burkholderia pseudomallei - Lowe, Peter (American Society for Microbiology (ASM), 2002)
The identification of Burkholderia pseudomallei, the causative agent of melioidosis, is usually not difficult in laboratories in areas where it is endemic. With the increase in international travel and the threat of bioterrorism, it has become more likely that laboratories in areas where it is not endemic could encounter this organism. The increase in the use of and dependence upon automated identification systems makes accurate identification of uncommonly encountered organisms such as B. pseudomallei critically important. This study compares the manual API 20NE and 20E identification systems with the automated Vitek 1 and 2 systems. A total of 103 B. pseudomallei isolates were tested and correctly identified in 98%, 99%, 99%, and 19% of cases, respectively. The failure of the Vitek 2 to correctly identify B. pseudomallei was largely due to differences in the biochemical reactions achieved compared to expected values in the database. It is suggested that this deficiency in the Vitek 2 may be due to the large number of uncertain results reported for these isolates. These results reduce the discriminating ability of the instrument to distinguish between uncommonly encountered isolates such as those of B. pseudomallei.